1967
DOI: 10.7883/yoken1952.20.175
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent Study on the Pathogenesis of Oral Infection of Poliovirus in Monkey

Abstract: SUMMARY : Cynomolgus monkeys were fed with a virulent strain of type 1 poliovirus (Mahoney), and the site of initial multiplication of the virus in the alimentary tract was investigated immunofluorescently.The virus antigen appeared as short as 24 hr after the feeding in both the squamous epithelial cells of the oropharynx and the macrophages of lymphatic structure of the tonsils. The virus antigen was also detectable at the early stage of infection in the reticulo-endothelial cells of the lamina propria of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Indirect evidence of viral replication in motor neurons of primates and mice has already been reported by other authors, who detected poliovirus by electron microscopy (Bodian, 1964;Blinzinger et aL, 1969), by immunofluorescence (Kovacks et al, 1963;Kanamitsu et al, 1967;Jubelt et al, 1980a) or by immunocytochemical methods (Hashimoto et al, 1984;Dal Canto et al, 1986). Using quantification of silver grains in motor neurons of monkeys paralysed after infection with virulent PV-1/$1-39-C6, we have shown that the maximum number of viral genomes found in degenerating motor neurons was quite similar to the maximum number of viral genomes in poliovirus-infected cells in vitro just before the cytopathic effect.…”
Section: Discussionmentioning
confidence: 60%
“…Indirect evidence of viral replication in motor neurons of primates and mice has already been reported by other authors, who detected poliovirus by electron microscopy (Bodian, 1964;Blinzinger et aL, 1969), by immunofluorescence (Kovacks et al, 1963;Kanamitsu et al, 1967;Jubelt et al, 1980a) or by immunocytochemical methods (Hashimoto et al, 1984;Dal Canto et al, 1986). Using quantification of silver grains in motor neurons of monkeys paralysed after infection with virulent PV-1/$1-39-C6, we have shown that the maximum number of viral genomes found in degenerating motor neurons was quite similar to the maximum number of viral genomes in poliovirus-infected cells in vitro just before the cytopathic effect.…”
Section: Discussionmentioning
confidence: 60%
“…Particles were also observed in mature macrophages, both in phagocytic vacuoles and apparently replicating in the cytoplasm. Indications that other picornaviruses replicate in the lamina propria have been noted by Kanamitsu et al (1967) and Heinz and Cliver (1989).…”
Section: G í4 Higher Magnification Of Inclusion (I) In Fig 13 Showmentioning
confidence: 76%
“…To date, whether epithelial or lymphoid cells are the primary sites of poliovirus replication in the gut has remained a matter of debate (4,9). Previously, fluorescence-labeled immunoglobulin from a poliovirus-infected macaque was used to detect poliovirus in epithelia or speculative macrophages after viral feeding (15). Technical difficulties, including nonspecific stain- Mahoney type 1 poliovirus.…”
Section: Resultsmentioning
confidence: 99%